THE CONVERSATIONAL IMPLICATURES USED BY THE MAIN CHARACTERS IN TWO BROKE GIRLS SERIAL MOVIE EPISODE ONE - DIAZWARA, ARINI PARAMITHA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Implicature, Conversational Implicature, Generalized ConversationalImplicature, Particularized Conversational Implicature, 2 Broke Girls. Human are social created, they need  to communicate to share information or ideas. In communication people were required to be cooperatively to make success communication, but sometimes some people do not speak cooperatively, and then they do not speak into the point of utterances’s meaning, it will makes the hearer feels confuse, then they try to imply the meaning, this phenomenon called implicature. This study attempts to analyze the conversational implicature on the dialogue of 2 Broke Girls movie based on Grice’s theory. There are two problems being formulated namely: (1) What are the types of conversational implicature found in 2 Broke Girls serial movie and (2) What are the implied meaning of implicature found in the utterances of 2 Broke Girls serial movie?This study uses qualitative descriptive approach because the writer analyzes the utterances produced by the main characters in 2 Broke Girls serial movie. The type of this research belongs to document analysis since the writer used the movie’s script as the data.In this research, the writer found that there are 30  utterances found in the dialogue of 2 Broke Girls serial movie. There are 10 utterances that contain Generalized Conversational Implicature, and there 20 utterances that contain Particularized Conversational Implicature. The result of the study is particularized implicature mostly occur in the utterances of this serial movie. Then, the writer explains the meaning based on the context of the uttrances that produced by the main characters.The writer suggests the next researchers conduct a reserch in serial movie or movie which has funny and unique implicture to make interesting analysis. It is hoped that the researchers or the students who are interested in studying implicature can get more knowledge about it.